2008
DOI: 10.1016/j.jvs.2008.01.057
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized trial of ACUSEAL (Gore-Tex) vs Finesse (Hemashield) patching during carotid endarterectomy: Long-term outcome

Abstract: Carotid endarterectomy with ACUSEAL patching and Finesse patching had similar stroke-free rates and stroke-free survival rates. The mean hemostasis time for the ACUSEAL patch was 1.4 minutes longer than that for the Finesse patch; however, the Finesse patch had higher restenosis rates than the ACUSEAL patch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…The perioperative stroke rates for both groups were comparable (2%). The long-term follow-up of the same study was also published recently, 40 which showed that the stroke-free survival rates were comparable for both patches, however, the freedom from Ն70% restenosis at 1, 2, and 3 years was 98%, 96%, and 98%, respectively, for ACUSEAL vs 92%, 85%, and 79% for the Finesse patch (P ϭ .04). The difference between the 5-minute hemostasis time for the ACUSEAL patch and the 3.7 minute hemostasis time for the Finesse patch was statistically significant, however, its clinical significance is debatable.…”
Section: Cea With Primary Closure Vs Patch Closuresupporting
confidence: 64%
See 1 more Smart Citation
“…The perioperative stroke rates for both groups were comparable (2%). The long-term follow-up of the same study was also published recently, 40 which showed that the stroke-free survival rates were comparable for both patches, however, the freedom from Ն70% restenosis at 1, 2, and 3 years was 98%, 96%, and 98%, respectively, for ACUSEAL vs 92%, 85%, and 79% for the Finesse patch (P ϭ .04). The difference between the 5-minute hemostasis time for the ACUSEAL patch and the 3.7 minute hemostasis time for the Finesse patch was statistically significant, however, its clinical significance is debatable.…”
Section: Cea With Primary Closure Vs Patch Closuresupporting
confidence: 64%
“…21,23,25,30,31,40,54 Unfortunately, our experience with the use of bovine pericardial patching has been limited, however, several recently published studies have confirmed a favorable clinical outcome using this patch after CEA. [55][56][57] Biasi et al 55 reported on their 9-year experience with the use of bovine pericardial patch angioplasty during CEA.…”
Section: Cea With Primary Closure Vs Patch Closurementioning
confidence: 99%
“…The demographic/clinical characteristics of these patients have been published previously. 9 When our standard velocity criteria (for nonoperated arteries -PSV of Ն140 c/s was optimal in detecting Ն50% stenosis) 5 were applied, 37% and 10% of patients were classified to have Ն50% to Ͻ70% and Ն70% to 99% restenosis vs 11.3% and 11.3% on CTA/angiography, respectively (P Ͻ .001, Kappa ϭ 0.4829, weighted Kappa ϭ 0.6334).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the comparison of these two patch materials were presented previously. 9 Both patches were 8 mm wide, manufacturerdesigned, and with a similar tapering at the end towards the ICA, ie, there was not any discrepancy in the size of both patches, and the length of both patches were comparable.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation